Prevalence of Anaemia in Sheep and its Associated Risk Factors in and Around Shivamogga, Malnad Region of Karnataka - Swamy, Niveditha Narayana; Revanna, Patel Suresh; Shekharappa, Pradeep Banagere; Gurubasappa, Ravindra Bhoyar; Ujjappa, Umesh Bandklara; Ballary, Shashidhar (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study examined the prevalence and risk factors of anaemia in sheep in Shivamogga region from March 2023 to February  2024. The study involved screening of 200 sheep of which 166 (83.00 %) were anaemic based on matching the conjunctival mucus  membrane with the CSWRI developed color chart. Anaemia was most common in sheep less than 6 months (87.25 %), and in female  sheep (84.82 %). Monsoon season had highest prevalence of anaemia (90.16 %) followed by post-monsoon (86.11 %) season, winter  (78.00 %) and least in summer (77.35 %). Based on aetiological agents the endo-parasitic infection was the most common cause  (96.00%), followed by ecto-parasitic infestation (81.60%) and least in mixed parasitic infection cases (69.23 %). Risk factors of anaemia  were found in animals reared by farmers with lack of awareness about deworming and acaricide, no education, not using dose based  on body weight, lack of acaricide usage, sheep shed with mud floors, extensive type of rearing, feed which included only green fodder  without concentrate and sheep drinking pond water all had higher rate of anaemia.
Keywords: Anaemia; CSWRI; Prevalence; Risk factors; Sheep; Shivamogga region